Critical Incidents for Hispanic Students on the Path to the STEM Doctorate - Horton, Dawn; Torres-Catanach, Irma (Frontiers in Psychology, 2022)
Hispanics are grossly underrepresented in the receipt of STEM Ph.Ds. The National Science Foundation (NSF) Science and Engineering Indicators (Trapani and Hale, 2019) suggest that only 7.8% of S and E doctoral recipients are Hispanic while their representation in the population is more than twice that, and that figure goes even higher if restricted to those within the college-age range. To address this gap, the NSF has awarded a grant (the Hispanic Alliance for Graduate Education and the Professoriate, H-AGEP) to the City College of New York and the University of Texas at El Paso to work with Hispanic STEM doctoral students to provide teaching training and preparation for academic positions so they can become role models for Hispanic community college undergraduates. In working to understand the career-decision making of our Fellows, in-depth interviews were conducted (n = 13) to understand what put them on the path to defy the odds and become a STEM doctoral recipient. Interview results suggest that isolated, critical incidents and chance events were responsible for a number of our students entering into doctoral programs. This research suggests that for some Hispanic STEM doctoral students the experience of chance events meant the path to a STEM doctorate was not assured from a young age and further, that the provision of “planned” critical incidents may support an increase in Hispanic STEM doctoral enrollment.